Improving leachate treatment by using limestone filtration and free water surface constructed wetland - Noor Shida , Mohd Noor (2012)
Landfill is the most applicable method in reducing the solid waste. However, the landfill method causes generation of leachate. Landfill leachate contains high levels of organic and inorganic matters which mean it is very contaminated. Due to this problem, leachate cannot be directly discharge into water course. Therefore, it is necessary for leachate to undergo a treatment process before it can be discharged into environment. This study mainly focused on the method of landfill leachate treatment. In this study, combination of limestone filter and free water surface wetland are used to treat landfill leachate. 5 to 15 mm particle sized of limestone and Eichhornia crassipes sp. (water hyacinth) as wetland plant were used to treat leachate. Raw leachate sample was collected from Jerangau-Jabor Landfill. The treated leachate was analyzed for BOD, COD, AN and total suspended solids improvement and heavy metal removal that consist of Fe, Cu, Cr, Mn, Zn and Pb. From the analysis, the combination of limestone filter and FWS constructed wetland was effective in treating landfill leachate. The result shows a great removal efficiency with 97.1% COD, 98.1% TSS, 97.6% A-N, 99.9% Fe, 99% Pb, 100% for Mn, Cu and Zn. Based on the study, it can be concluded that the combination of limestone filter and FWS constructed wetland has a high efficiency in removing leachate pollutants. The optimum contact time for the system is seven days.